Role of communication in CRM solution implementations - Mukerjee, Hory Sankar; Prasad, U Devi (Gyan Management Journal, 2017)
Communication plays a very critical role in business, and so does it in project management. Projects reportedly have failed due to poor or inadequate communication. The subject of CRM implementations are of importance in the current business environment primarily because of the significance it has. Implementing of CRM, especially the technology implementation often rests with and IT service provider. Therefore it is quite possible that gaps exist between the company implementing CRM and the IT service provider. The gap therefore needs to bridged by communicating. However the bigger challenge is that communication is never taken 'formally' or even 'seriously' in IT project management. The focus lies more on project management, and achieving the iron triangle of the project success. The purpose of this research article therefore is to understand how communication impacts CRM solution implementations, if there is a real impact and what are the factors that needs to be looked at while communicating during CRM solution implementations. This research has been conducted from the perspective of the IT project management team and the role that communication would play for them for effective project management and engagement.
Keywords: CRM; Technology; Solutions; Communication